Smoking trajectories from adolescence to early adulthood as a longitudinal predictor of mental health in adulthood: evidence from 21 years of a nationally representative cohort. (9th December 2021) - Lee, Boram; Levy, Douglas E.; Macy, Jonathan T.; Elam, Kit K.; Bidulescu, Aurelian; Seo, Dong‐Chul
Abstract: Aims: To measure the prospective relationship between smoking trajectories from adolescence to young adulthood and mental health in later adulthood and test whether this relationship was mediated by concurrent co‐use of alcohol and marijuana. Design: Longitudinal study using data drawn from rounds 1 to 18 of the National Longitudinal Survey of Youth 1997 (NLSY97), a nationally representative cohort study spanning 21 years. Setting: United States. Participants: The analytical sample included those who completed survey items about smoking behaviors on at least half the data collection opportunities in adolescence and young adulthood ( n = 8570, 48.9% female, 66.2% white). Measurements: Mental health in adulthood was measured using the five‐item Mental Health Inventory (MHI‐5; range = 0–100) at round 18. Seven trajectories of smoking from adolescence to young adulthood were identified by group‐based multi‐trajectory modeling, using data over 11 years from rounds 1 to 11. Findings: Late‐onset moderate smokers [β = −1.95, 95% confidence interval (CI) = −3.61 to −0.29], late‐onset accelerated smokers (β = −2.53, 95% CI = −4.28 to −0.78), early‐onset heavy smokers (β = −3.72, 95% CI = −5.59 to −1.85) and early‐onset moderate smokers (β = −2.66, 95% CI = −4.48 to −0.84) showed poorer regression‐adjusted mean MHI‐5 scores in later adulthood than stable abstainers, even after controlling for baseline mental health and covariates. Whether or not a difference in MHI‐5 scores was present between quitters and stable abstainers was inconclusive. The concurrent co‐use of alcohol and marijuana in young adulthood significantly mediated the relationship between smoking trajectory and mental health. Conclusions: Continued smoking, especially early‐onset and heavy smoking from adolescence to young adulthood, appears to increase the risk of poor mental health later in mid‐adulthood, and quitting smoking in young adulthood may mitigate such risk even among early‐onset smokers. Mediation analyses underscore the role of using multiple substances in this pathway.